STRATEGY DEVELOPMENT FOR CREATING COMPETITIVE ADVANTAGES IN SMALL AND MEDIUM INDUSTRIES (SMIs) - Anggadwita, Grisna; Fitria, Sisca Eka; Suyono, Rega Eggitya (Jurnal Aplikasi Manajemen, 2019)
Currently, the increasingly dynamic industry development has caused business competition that cannot be avoided by business players, including by TRI as one of the SMIs in Purbalingga Regency, Indonesia. TRI is a business engaged in the automotive field by producing racing exhausts. This study aims to identify the development of competitive strategies carried out by TRI by analyzing the external and internal environment. This research uses the descriptive qualitative method with a case study approach. The sampling technique in this study uses purposive sampling by conducting depth interviews with key people who are considered to know and understand the business processes of TRI. The analysis technique uses EFE, IFE, SWOT, and QSPM matrices. The results show an EFE Matrix score of 2.86 and an IFE Matrix score of 2.88 so that the TRI position is in the IE Matrix on cell V with the priority strategy being to hold and maintain. Based on the SWOT matrix results, the company has five alternative strategies, consisting of 4 market penetration strategies and 1 product development strategy. Alternative strategies that become the top priority based on the QSPM matrix evaluation are market penetration strategies. The recommendations and implications of this study are discussed further.